Hypoxia-inducible factor-prolyl hydroxylase inhibitors for treatment of anemia in chronic kidney disease: a systematic review and network meta-analysis - Ren, Song; Zhao, Yurong; Wu, Jingyu; Ren, Shangqing; Feng, Yunlin (Frontiers in Pharmacology, 2024)
Purpose To review current evidence on the efficacy and safety outcomes of HIF-PHIs in chronic kidney disease (CKD) populations with an emphasize on the safety profile.Methods A systematic search was conducted in the Medline, Embase, and Cochrane Central databases. Randomized controlled trials that had assessed the efficacy and safety of HIF-PHIs for anemia in CKD were included. The efficacy outcome included change of hemoglobin and the safety outcomes any adverse events, severe adverse events, major adverse cardiovascular events, and mortality. The qualities of studies were assessed using the Cochrane ROB tool.Results 47 studies encompassing 55 RCTs for the study outcomes were included in this study. All six commercially available HIF-PHIs had direct comparisons to ESA and placebo, yet lacked direct comparisons among each other. The network analysis demonstrated all six HIF-PHIs were able to effectively elevate hemoglobin in the general CKD patients compared to placebo. All HIF-PHIs did not differ among each other in the efficacy of correcting anemia. Roxadustat and daprodustat had the largest number of reports in terms of adverse events. The overall risk of each safety outcome did not increase in comparison to erythropoiesis stimulating agent (ESA) or placebo, and did not differ among different types of HIF-PHIs.Conclusions HIF-PHIs can effectively elevate hemoglobin without causing higher risk of safety concerns in CKD patients with anemia. Further evidence from long-term studies and the ongoing post-market surveillance is necessary.